Innovative Approaches in Developing Multicultural-Based Islamic Religious Education Curriculum - Afif, Nur; Qowim, Agus Nur; Mukhtarom, Asrori (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2025)
This article will describe the innovation of a multicultural-based Islamic Education curriculum in Madrasah Tsnawaiyah An Namiyah Pondok Aren. Therefore, the focus of the problems raised in this study are; how is the PAI curriculum multiculturally based? How are the innovations made in the multicultural-based PAI curriculum at Madrasah Tsanawiyan An Namiyah Pondok Aren? This research was conducted conceptually, where the author collected research data from existing literacy, related to the theme raised, then reviewed it narrative-descriptively. The results showed that the multicultural-based PAI curriculum at MTs An Namiyah Pondok Aren adjusted to aspects of student development. At this stage, PAI subjects at MTs An Namiyah Pondok Aren already reflect multicultural values, namely students are able to maintain mutual understanding, and show mutual respect. At this stage students are able to get to know themselves by discussing with others, who are culturally different. This is so that students can distinguish the multicultural aspects around them (school), and be able to participate in life. The effort to instill a multicultural attitude is carried out with three approaches, namely contributive, additive, and social action.